Molecular and Cellular Basis of Microvascular Perfusion Deficits Induced by Clostridium perfringens and Clostridium septicum - Hickey, Michael J. (Public Library of Science, 2008)

(untitled)
Reduced tissue perfusion leading to tissue ischemia is a central component of the pathogenesis of myonecrosis caused by Clostridium perfringens. The C. perfringens α-toxin has been shown capable of inducing these changes, but its potential synergy with perfringolysin O (θ-toxin) is less well understood. Similarly, Clostridium septicum is a highly virulent causative agent of spontaneous gas gangrene, but its effect on the microcirculation has not been examined. Therefore, the aim of this study was to use intravital microscopy to examine the effects of C. perfringens and C. septicum on the functional microcirculation, coupled with the use of isogenic toxin mutants to elucidate the role of particular toxins in the resultant microvascular perfusion deficits. This study represents the first time this integrated approach has been used in the analysis of the pathological response to clostridial toxins. Culture supernatants from wild-type C. perfringens induced extensive cell death within 30 min, as assessed by in vivo uptake of propidium iodide. Furthermore, significant reductions in capillary perfusion were observed within 60 min. Depletion of either platelets or neutrophils reduced the alteration in perfusion, consistent with a role for these blood-borne cells in obstructing perfusion. In addition, mutation of either the α-toxin or perfringolysin O structural genes attenuated the reduction in perfusion, a process that was reversed by genetic complementation. C. septicum also induced a marked reduction in perfusion, with the degree of microvascular compromise correlating with the level of the C. septicum α-toxin. Together, these data indicate that as a result of its ability to produce α-toxin and perfringolysin O, C. perfringens rapidly induces irreversible cellular injury and a marked reduction in microvascular perfusion. Since C. septicum induces a similar reduction in microvascular perfusion, it is postulated that this function is central to the pathogenesis of clostridial myonecrosis, irrespective of the causative bacterium.